Towards a better quality education in engineering and technology in developing countries - OUKIL, M.S.; DAMOU, M (Journal of Human Sciences, 2002)
In theory, it is by now very much clear and widely accepted that science and technology are necessary for progress and welfare. But, it is essential to point out here that in fact they have no real impact unless if they are applied to development at points of production. It therefore follows that allocated financial and human resources should be used and managed in a way as to maximise such an impact. Any action against this will result in wasting and costs. In practice, and as far as developing countries are concerned, overall and technological performances are unfortunately not generally good. For, despite ambitious programmes and important investments made in the fields of technology transfer and education, only a few of those countries have succeeded in reducing the so called ‘technological gap’ and realised technological take-off. ملخصنظريا إنه جد معروف وواضح الآن أن العلم والتكنولوجية هما ضروريان للتقدم و الرفاهية. غير أنه من اللازم الاشارة هنا إلى عدم فعاليتهما إلا إذا طبقا في مواقع الإنتاج. وعلى هذا الأساس، يفترض أن توجه وتسير الموارد المالية والبشرية بطريقة بحيث تعظم أثرهما. من جهة أخرى وعمليا، فإن الأداء العام والتونولوجي بالبلدان النامية ليس جيدا على العموم. هذا بإعتبار أنه رغم البرامج الجد طموحة و الاستثمارات الهامة المسخرة في مجال العلم و التمنولوجية، إلا أن عددا قليلا فقط من تلك البلدان. استطاعت أن How could one, then, explain this situation? This is exactly what this joint paper is concerned with. Based on some available data and practical observations of their country (Algeria), its authors attempt to add another explanation to what is actually provided in the literature about the issue. For them, the real problem has to do mainly with the way or manner with which the issue has been treated and managed. In brief, particular lack of flexibility and interactive facilities affect necessarily institutions’ good functioning and overall performance.